Structural, morphological and Optical properties of copper Oxide thin film - Akhlas Emad Ali Aswad; Ruqaya Dyaa Abd Alhameed Abd Almajeed; Hawraa Hatam Saheb Sabah; Rashad Suhayb Yahya Abdullah (Genius Journals, 2024)
From this work we conclude the following mean outcomes: • Copper oxide thin films have been prepared by low cost using pulsed laser deposition technique on glass slide substrate . • Polycrystalline structure with three phases cubic Cu, monoclinic CuO and cubicCu2O were obtained from using X-ray diffraction (XRD) analysis • Homogeneous distribution nano particles with average diameter 68.86 nm and root mean square roughness of 0.67 nm were found from the atomic force microscope measurement . • The optical characteristics showed that the prepared CuO thin film has a direct allow electronic transition with 2.5 eV optical energy gap (Eg) • These properties make the material more prominent for device applications of various optoelectronics and photonic devices
Keywords: Morphological; properties; chopper Oxide